2000
DOI: 10.1016/s0163-6383(00)00032-1
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in human neonatal social perception

Abstract: Sexual dimorphism in sociability has been documented in humans. The present study aimed to ascertain whether the sexual dimorphism is a result of biological or socio-cultural differences between the two sexes. 102 human neonates, who by definition have not yet been influenced by social and cultural factors, were tested to see if there was a difference in looking time at a face (social object) and a mobile (physical-mechanical object). Results showed that the male infants showed a stronger interest in the physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
249
3
14

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 390 publications
(289 citation statements)
references
References 12 publications
9
249
3
14
Order By: Relevance
“…For example, it has been observed that female neonates look more at faces compared to male neonates (Connelan, Baron-Cohen, Wheelwright, Batki, & Ahluwalia, 2000). Also, female infants look more at a human face on their first day of life whereas male infants look more at the mechanical mobile suspended above them (Connelan et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been observed that female neonates look more at faces compared to male neonates (Connelan, Baron-Cohen, Wheelwright, Batki, & Ahluwalia, 2000). Also, female infants look more at a human face on their first day of life whereas male infants look more at the mechanical mobile suspended above them (Connelan et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been observed that female neonates look more at faces compared to male neonates (Connelan, Baron-Cohen, Wheelwright, Batki, & Ahluwalia, 2000). Also, female infants look more at a human face on their first day of life whereas male infants look more at the mechanical mobile suspended above them (Connelan et al, 2000). Moreover, it has been found that higher prenatal testosterone levels diminish the amount of eye contact a child would make years later (Baron-Cohen, Knickmeyer, & Belmonte, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…We asked the proposer to assign a probability to the acceptance of the offer he or she actually proposed. 10 The proposer typed a single probability of acceptance (π k a ). Proposers were rewarded using a quadratic scoring rule described in Appendix B.…”
Section: Belief Elicitation Phasementioning
confidence: 99%
“…Remember that these are the responder's belief that he or she will receive every potential offer (90, 80, 70, 60, 50,40,30,20,10). Since only one such amount will actually be sent, the payoff to player Y (the responder) when the amount m is chosen will be:…”
Section: Game Instructions Both Gamesmentioning
confidence: 99%
“…Second, the way the mother interacts with the child may differ from the way the father interacts with the child (Achenbach et al, 1979). Another cause for different views in parent reports could be that men are more sensitive to different kinds of input from their children than women (Baron-Cohen & Hammer, 1997;Connelan et al, 2000;Rosenthal et al, 1979).…”
mentioning
confidence: 99%